Depression among military spouses: Demographic, military, and service member psychological health risk factors. Issue 12 (13th August 2018) - Donoho, Carrie J.; LeardMann, Cynthia; O'Malley, Christopher A.; Walter, Kristen H.; Riviere, Lyndon A.; Curry, John F.; Adler, Amy B.
Abstract : Background: More than a decade of war has strained service members and their families and the psychological health of military spouses is a concern. This study uses data from the largest study of military families in the United States to examine the demographic, military‐specific, and service member mental health correlates of probable diagnosis of major depressive disorder (MDD) among military spouses. Methods: Data were from service member‐spouse dyads from all branches of the U.S. military. Demographic and military‐specific factors were assessed using administrative personnel records and survey data. Results: Of the 9, 038 spouses, 4.9% had a probable diagnosis of MDD. In unadjusted models, spouses of service members who deployed and experiencecd combat‐related events, were enlisted, had a probable posttraumatic stress disorder (PTSD) diagnosis, or screened positive for alcohol misuse were more likely to screen positive for MDD. In adjusted models, only spouses married to enlisted service members or those with PTSD had increased risk for MDD. Other demographic and military‐related factors associated with MDD in spouses included less educational attainment, unemployment, having four or more children, and having prior military service (although not currently serving in the military) in the adjusted models. Conclusions: Findings characterize demographic, military, and service member psychological health factors that are associated with depression among military spouses. These findings imply that deployment alone may not negatively affect military spouses, but rather it may be the mental health impact on the service member, especially PTSD that increases the odds for MDD among military spouses.